Análise do comportamento de gabiões eletrosoldados: tecnologia sustentável para infraestrutura de cidades inteligentes - Cruz, Flávio Fontes da (2025)
In recent years, several Brazilian municipalities have experienced natural disasters. The financial damage caused by these incidents has run into hundreds of billions of reais. These calamities directly affect the population, with many people left homeless and displaced, as well as the cities themselves, which see their urban infrastructures affected, in need of repairs and especially new construction. Due to the high population density and occupation in regions with high geological risk, landslides and slope instability are common and lead to the need for containment constructions. Among the various options, gabion retaining walls are a sustainable, low-cost and safe construction solution for use in these areas. Given the relevance of these gabion constructions, this research carried out unconfined simple tensile and compressive tests on electrowelded mesh gabions filled with gravel, and also evaluated the use of 4 sensors to monitor an electrowelded gabion retaining wall in the municipality of Jacareí/SP over a 30 day period. The instruments used IoT (Internet of Things) technology and provided readings of horizontal displacements in the retaining wall (overturning), in order to assess the feasibility of their use, as well as the sensors' ability to read and send data. The results will allow public authorities, professionals and academics to have access to the performance and deformation of these materials, as well as analyzing the feasibility of using sensors in gabion retaining walls, allowing better use of these solutions according to the specifications of each type of work.